2022
DOI: 10.1007/s12187-022-09960-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Outcomes of Under-five Children of Smallholder Farm Households: Do Higher Commercialization Levels Lead to Better Nutritional Status?

Abstract: The study investigated the nutritional status of under-five children of farm households. The study utilized primary data from 352 farm households with 140 under-five children. Household crop commercialization index (CCI) was used to estimate cassava farm household crop sale ratio and categorize the households into four commercialization levels while WHO Anthro software was employed to analyze under-five children anthropometric indices such as weight-for-age z-score (WAZ), height-for-age z-score (HAZ) and weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
2
1
Order By: Relevance
“…Also, the crop sold ratio (cassava commercialization variable) was not statistically significant, indicating that CCI levels of farm households was not one of the influencing factors determining the nutritional status of adult men. This finding was contrary to other studies that reported that CCI levels of farm families was one of the influencing factors determining the malnutrition status of under-5 [ 4 ] and adolescents in Southwestern Nigeria [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also, the crop sold ratio (cassava commercialization variable) was not statistically significant, indicating that CCI levels of farm households was not one of the influencing factors determining the nutritional status of adult men. This finding was contrary to other studies that reported that CCI levels of farm families was one of the influencing factors determining the malnutrition status of under-5 [ 4 ] and adolescents in Southwestern Nigeria [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies in Africa have focused on the dietary diversity (DD) of women especially those of child bearing age category [ 11 , [20] , [21] ] and others, from the perspective of under-five children of agricultural and non-agricultural households [ 3 , [22] , [23] ]. Further, some studies investigated DD of some other age groups in the households such as adolescents [ 3 , 24 , 25 ] while studies regarding the nutritional status (NS) of members of household have also been given some level of priority in literature [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the prevalence of undernourishment increased globally from 9.3% in 2020 to 9.8% in 2021 under the influence of COVID-19 pandemic [9]. Meanwhile, Africa remained the region with the heaviest burden of hunger having 278 million (20.2%) of the population affected by hunger in 2021 [9,10]. In Nigeria, the recent food insecurity situation calls for immediate humanitarian intervention with rising number of undernourished people coupled with an estimated 41 percent of the population living in extreme poverty [11,12].…”
Section: Introductionmentioning
confidence: 99%